Variability in sulfur isotope composition suggests unique dimethylsulfoniopropionate cycling and microalgae metabolism in Antarctic sea ice. (December 2018) - Carnat, Gauthier; Said-Ahmad, Ward; Fripiat, François; Wittek, Boris; Tison, Jean-Louis; Uhlig, Christiane; Amrani, Alon
Abstract Sea ice microbial communities produce large amounts of the sulfur metabolite dimethylsulfoniopropionate (DMSP), a precursor of the climate cooling gas dimethylsulfide. Despite their importance to the polar sulfur cycle, drivers and metabolic pathways of sea ice DMSP are uncertain. Here we report the first measurements of sea ice DMSP sulfur isotopic composition (34 S/32 S ratio, δ34 S). δ34 S values in ice cores from the Ross Sea and Weddell Sea reveal considerable variability across seasons and between ice horizons (from +10.6 to +23.6‰). We discuss how the most extreme δ34 S values observed could be related to unique DMSP cycling in the seasonally extreme physiochemical conditions of isolated brine inclusions in winter-spring. Using cell cultures, we show that part of the DMSP δ34 S variability could be explained by distinct DMSP metabolism in sea ice microalgae. These findings advance our understanding of the sea ice sulfur cycle and metabolic adaptations of microbes in extreme environments. Gauthier Carnat et al. report the first measurements of the natural sulfur isotopic composition of sea ice from the Antarctic. They find considerable variability between seasons and sea ice horizons, suggesting unique cycling of sulfur metabolites by sea ice microalgae in extreme environments, with important implications for the production of gasses that impact global climate.